PELATIHAN TEKNIK PENGELASAN DAN MANAJEMEN USAHA PADA UKM) COR LOGAM BUANA JAYA DAN KALINDA IRON DI KECAMATAN CEPER, KABUPATEN KLATEN - Sunarto Sunarto; Feri Setyowibowo; Harini Harini (Department of Economics Education, Universitas Sebelas Maret, 2017)
Science and Technology for Society (IbM) is conducted on Small and Medium Enterprises (SMEs) named Cor Logam Buana Jaya and Cor Metal Kalinda Iron. The two SMEs are located in Ngawonggo Village, Kecamatan Ceper, Klaten Regency. The first SMEs, Cor Logam Buana Jaya produces art casting (indoor and outdoor furniture) in the form of metal products such as ornaments or decoration products, while the second, Cor Metal Kalinda Iron produces the machinery spare parts products (technical goods) that are various products of machining and automotive spare parts. This activity aims to improve the quality of metal production and welding techniques, as well as improve the quality of bookkeeping and management in both partner SMEs. The method used in this activity is a participatory training and supervision method. Based on the evaluation results, this training has a positive impact on the development of participants' skills and SMEs operation. It is proved that the participants are able to understand the material presented, able to know and overcome the problems that have been faced, and able to practice welding technique on stainless metal and financial management on SMEs much better.